A Practical EDP Audit/Retrieval System for Education. - Lampe, James C. (The Accounting Review, 1978)
ABSTRACT: Most accounting curricula do not provide students with practical reinforcement of EDP audit/retrieval system concepts. This paper reports on a computer program package that has been designed to fill this educational void. The MARS package consists of five different routines that enable students to gain hands-on experience similar to many features of larger commercial audit/retrieval systems. Student testing of the package and related case studies has proven them to be effective and efficient pedagogical tools.